Missing outcome data in randomised clinical trials of psychological interventions: a review of published trial reports in major psychiatry journals - Sophie Juul; Pascal Faltermeier; Johanne Juul Petersen; Markus Harboe Olsen; Rebecca Kjaer Andersen; Caroline Barkholt Kamp; Faiza Siddiqui; Sebastian Simonsen; Lawrence Mbuagbaw; Lehana Thabane; Janus Christian Jakobsen (BMC Psychiatry)
Abstract Background Missing outcome data can pose a serious threat to the validity of randomised clinical trial results. We aimed to study the extent of missing outcome data in randomised clinical trials of psychological interventions. Methods We performed a retrospective study of randomised clinical trial reports of psychological interventions published in World Psychiatry, JAMA Psychiatry, Lancet Psychiatry, American Journal of Psychiatry, British Journal of Psychiatry, or Psychotherapy and Psychosomatics from 2017 to 2022. We assessed the proportion of missing outcome data, whether missing data patterns differed between types of outcomes, participants, intervention lengths, and psychological intervention types, how missing outcome data were handled in the statistical analyses, and whether trialists discussed missing outcome data in the discussion section of the manuscript. Results We identified 182 randomised clinical trials (233 primary outcomes), of which 206 outcomes (88.4%) were assessed at high risk of bias due to missing data. The overall mean percentage of missing outcome data was 18.3% (95% confidence interval (CI): 16.7–20%) for all outcomes. The percentages of missing data were 18.9% (95% CI: 17.1–20.6%; 180 outcomes) for symptom severity scales and 1.8% (95% CI: 2.3–3.3%; 6 outcomes) for ‘hard’ binary outcomes. Trials including participants with borderline personality disorder had the highest percentage of missing outcome data (33.1%; 95% CI: 22.3–43.9%) compared with other psychiatric disorders. Fisher’s exact test showed that intervention lengths and psychological intervention types were associated with the proportion of missing outcome data (p < 0.001), but there were no clear patterns. Conclusion Missing outcome data is a considerable problem in randomised clinical trials of psychological interventions, and trialists should consider the corresponding methodological limitations in the design and analysis to reduce the risk of bias due to missing outcome data. Clinical trial registration number Not applicable.